Desain Prototype Alat Filtrasi Sederhana dari Limbah Galon Air untuk Pembuatan Penyaringan Air Rumah Tangga - Ferdi Ferdi; Rosdiana Rosdiana; Wa Ndibale; Moch. Assiddieq; Ilham; Dwiprayogo Wibowo (FAKULTAS TEKNIK UMKENDARI, 2022)
This study reports on the utilization of gallons of water used as containers for household-scale water purification filtration devices. The method of making a filtration device is by making a tap hole (outlet) at the bottom of the gallon and then putting in a filter material consisting of gravel, fine sand, charcoal, coarse sand, sponges, and palm fibre. A water filtration system by entering the water in the top hole of the gallon and the filtered water results are located at the bottom of the gallon that has been given a faucet. Based on the results of this study, it is shown that a gallon waste water-based filtration system is effective in the water filtration process at housing X in Kendari City. Test parameters consisting of turbidity, color, total dissolved solids (TDS), acidity (pH), and iron (Fe) content showed that the decrease in content that occurred in each turbidity test was 56.77%, color 33.33%, TDS 33.61%, the pH level increased by 4.21% (7.37 to 7.68) due to the effect of reduced levels of carbon dioxide (CO2) in water from the filtration process and categorized as water that is suitable for health. Fe levels did not change significantly, where there was an increase of 1.2% (25.7 × 10-4 mg.L-1 to 26.0 × 10-4 mg.L-1). The results of this study illustrate that gallons of water waste can be used as a material for making simple filtration equipment for household-scale water filtration processes.